Corruption, Global Security, and World Order - Rotberg, Robert I. (Book collections on Project MUSE., 2009)
"Discusses global ramifications of deeply embedded corruption by criminals and criminalized states. Explores trafficking issues--how nuclear/WMD smugglers coexist with other traffickers. Examines how corruption deprives citizens of fundamental human rights, assesses the connection between corruption and the spread of terror, and proposes remedies to reduce and contain corruption"--Provided by publisher